Analysis of teaching and learning in physical education - Veal, Mary Lou (Jones & Barlett Learning, 2011)
Analysis of Teaching and Learning in Physical Education presents research-based best practices for teaching physical education in order to help pre-service and practicing teachers improve their skills through analysis and reflection. The text begins with an informal analysis of teaching and then quickly moves into systematic strategies for analyzing student and teacher behaviors and interactions. Based on Bill Anderson s groundbreaking work, Analysis of Teaching Education (1980), this text is designed to help physical education teachers meet NASPE s Standards for Advanced Programs in Teacher Education.